Teacher collaboration’s influence on inquiry-based science teaching methods - Céline Lepareur (Education Inquiry, 2018)
Developing inquiry-based science teaching (I.B.S.T.) methods in lower secondary schools challenges many schools and educational bodies. The paper addresses the influence of teacher collaboration on science teachers’ approaches and practices regarding I.B.S.T. The research emphasises three case studies: two science teachers, one expert and one new teacher, attending programmes based on teacher collaboration; one experienced teacher without any specific training on I.B.S.T.. Each of the three teachers was videotaped during one classroom session and interviewed about the video directly after the lesson. Their practices were portrayed in terms of the six crucial dimensions and indicators of I.B.S.T. Differences were seen among the three teachers. The two teachers attending programmes based on teacher collaboration employ teaching approaches and practices with greater emphasis on learning and learners. The isolated teacher’s approaches and practices are more content- and teacher-centred. These findings concurred with quantitative results from the broader sample from which the case study was drawn. Outcomes concerning teacher training are discussed.